Aspergillus niger CSR3 regulates plant endogenous hormones and secondary metabolites by producing gibberellins and indoleacetic acid. Issue 1 (1st January 2018) - Lubna; Asaf, Sajjad; Hamayun, Muhammad; Gul, Humaira; Lee, In-Jung; Hussain, Anwar
ABSTRACT: In this study, an endophytic fungus, Aspergillus niger CSR3, was isolated from Cannabis sativa . The culture filtrate (CF) was initially screened for growth-promoting activities such as the presence of siderophores, phosphate solubilization, and the production of indole acetic acid (IAA) and gibberellins and was further assayed for its ability to promote the growth of mutant waito -C rice. Nearly all plant growth attributes examined (root–shoot length, biomass, and chlorophyll content) were significantly enhanced by treatment with CSR3. This growth promotion action was due to the presence of various types of gibberellins (GAs) and IAA in the endophyte CF. Moreover, the presence of GA pathway genes ( P50-1, P450-3, P450-4, ggs2, and des ) was confirmed by means of semi-quantitative RT-PCR. Finally, the application of CSR3 spore suspension with uniconazole and yucasin on maize seedlings revealed that, similar to exogenous IAA and GA3, CSR3 has the potential to alleviate the inhibitory effect of these inhibitors.